2020
DOI: 10.1039/c9ew00967a
|View full text |Cite
|
Sign up to set email alerts
|

Microrespirometric assessment of the metal–organic framework [Co2(btec)(bipy)(DMF)2]n (“MOF-Co”) to prevent inhibition by arsenic in activated sludge

Abstract: This study, for the first time, presents the application of a microrespirometric method to evaluate the effect of MOF-Co and As(iii) on biological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition, MOF products have been successfully used in the adsorption of organic compounds. Therefore, more studies are necessary to assess the efficiency and nano-safety of these material types due to their versatility (51). A study conducted on the nanocarrier system had effectively delivered antitumor and retroviral anti-cancer and AIDS medication by non-toxic, porous iron (III) based MOFs (such as MIL-53, MIL-88, MIL-88Bt, MIL-89, MIL-100, and MIL-101 NH2) (52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MOF products have been successfully used in the adsorption of organic compounds. Therefore, more studies are necessary to assess the efficiency and nano-safety of these material types due to their versatility (51). A study conducted on the nanocarrier system had effectively delivered antitumor and retroviral anti-cancer and AIDS medication by non-toxic, porous iron (III) based MOFs (such as MIL-53, MIL-88, MIL-88Bt, MIL-89, MIL-100, and MIL-101 NH2) (52).…”
Section: Discussionmentioning
confidence: 99%
“…), showing in some cases high structural stability [ 15 , 16 ]. In addition, it has been reported that Co MOFs in some cases do not cause toxicity on microorganisms and exhibit a low cytotoxic effect towards in a liver cell line (LO2) [ 17 , 18 ]. For example, Ordaz et al [ 17 ], through microrespirometric studies on activated sludge in the presence of a cobalt-based organic metal compound (MOF-Co), found that this material did not inhibit oxygen consumption of the activated sludge.…”
Section: Introductionmentioning
confidence: 99%